Rola Jacka Kuronia w procesie odradzania się idei społeczeństwa obywatelskiego w Polsce - Kaszkur, Alina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
Without doubt, Jacek Kuroń was an outstanding figure in the recent history of Poland. His political platform made a considerable contribution to the development of the organization and political strategy of opposition circles and was equally important in the revival of the idea of civic society in Poland. His whole life long, Kuroń struggled to make the individual central by means of involvement in the organized life of the community. He perceived a civic society as such a community, driven by moral standards and a common good, united by brotherhood, spontaneously organizing itself and shaping its own awareness and attitudes. During the period of his social and political activity Kuroñ struggled to revive the idea of a civic society both under the communist system, and later in a revived independent Poland. The projects he proposed were always preceded by a thorough assessment of the reality that surrounded him, and adapted both to the contemporary political circumstances and the social mood. Kuroń’s postulates were intended to make the society sensitive to the need to care for the common good, to inspire a feeling of responsibility for the state, and they called for social, cultural, economic and political activity, encouraging citizens to participate in running their own country.